UJI AKTIVITAS ANTIHIPERURISEMIA EKSTRAK ETANOL DAUN BUNI (Antidesma bunius L.) PADA MENCIT PUTIH (Mus musculus L.) JANTAN - Sulastri Herdaningsih; Khizul Hertiani (Jurnal Komunitas Farmasi Nasional, 2025)
Hyperuricemia is a condition characterized by elevated levels of uric acid in the blood, which can lead to diseases such as gout arthritis. This study aims to evaluate the activity and effective dose of ethanolic extract of buni leaves as ananti-hyperuricemic agent in male white mice (Mus musculus L.) induced with potassium oxonate and chicken liver juice. A total of 25 mice were divided into five groups: positive control (allopurinol 100 mg/kgBW), negative control (0.5% Na-CMC), and three test groups receiving buni leaf extract at doses of 50 mg/kgBW, 75 mg/kgBW, and 100 mg/kgBW,respectively. Uric acid levels were measured over a period of 4 hours after treatment. The results showed that the positivecontrol group and all groups treated with buni leaf extract at doses of 50, 75, and 100 mg/kg BW exhibited antihyperuricemic activity, as indicated by a significant difference compared to the negative control group (p<0.05). Thepercentage of antihyperuricemic activity reached 100% in the positive control group and all buni leaf extract groups. It can thus be concluded that the ethanolic extract of buni leaves has potential as an antihyperuricemic agent. Keywords: Buni leaves (Antidesma bunius L.), anti-hyperuricemia, uric acid, mice (Mus musculus).